The Analysis Study Of Chronic Kidney Disease After Acute Kidney Injury: A Comprehensive Systematic Review - Wirawan, Nugraha; Pazka, Khoirunnisa Sarabayan (International Medical Journal Corp. Ltd, 2024)
Background: The relationship between Acute kidney injury (AKI) and CKD is complex, with chronic kidney disease (CKD) being a risk factor due to reduced renal reserve and stress-related issues. AKI can initiate or accelerate CKD development, leading to maladaptive repair mechanisms and a growing public health burden. This systematic review aims to analyze current evidence on the risk of CKD development after AKI based on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Acute kidney injury (AKI) is a precursor to chronic kidney disease (CKD), impacting long-term renal health. Even mild episodes contribute to sustained glomerular filtration rate reductions, suggesting incomplete recovery and a narrow intervention window for prevention.